Cangrelor PK/PD analysis in post‐operative neonatal cardiac patients at risk for thrombosis. (29th November 2020) - Vargas, Diana; Zhou, Hairu; Yu, Xinren; Diamond, Scott; Yeh, Justin; Allada, Vivekanand; Krishnamurthy, Ganga; Price, Mary; Allen, Beverly; Alexander, James; Schmidhofer, Joseph; Kreutzer, Jacqueline; et al.
Abstract : Essentials An optimal therapeutic strategy has yet to be established to prevent early shunt thrombosis. A phase 1 study of cangrelor was performed in neonates after palliation of congenital heart disease. PD endpoint of >90% platelet inhibition in 60% of patients was achieved at 0.5 µg/kg/min dosing. No serious adverse events related to drug administration were observed, including bleeding. Abstract: Background: Systemic‐to‐pulmonary artery shunt thrombosis is a significant cause of early postoperative mortality in neonates after palliation of congenital heart disease. In the context of thromboprophylaxis, an optimal therapeutic strategy has yet to be established before aspirin administration. Cangrelor, a fast‐acting, reversible P2Y12 inhibitor, may fill this unmet need. Objectives: To evaluate the pharmacokinetics (PK), pharmacodynamics (PD), and safety of cangrelor in neonates undergoing stage 1 palliation. Methods: This prospective, open‐label, single‐arm study evaluated two cangrelor dosing cohorts following placement of a systemic‐to‐pulmonary artery shunt, right ventricle‐to‐pulmonary artery shunt, or ductal stent. Drug concentrations and platelet reactivity, assessed by light transmission aggregometry and in microfluidic assays (MF), were measured. Results: Twenty‐two patients were consented and 15 received a 1‐hour infusion of cangrelor at either 0.5 µg/kg/min (cohort 1) or 0.25 µg/kg/min (cohort 2). Whereas the primary PD endpoint was achieved at the higher dose (ie, reduction in maximal platelet aggregation by ≥90% in 60% of participants), only 29% of those in cohort 2 attained this goal. Comparable and statistically significant results were obtained in MF assays ( P  < .0001 vs. baseline). Drug levels during infusion were 3‐fold higher in cohort 1 vs. cohort 2 ( P  < .001). Most participants (70%) had undetectable drug levels by 10 minutes postinfusion with full recovery in platelet function at 1 hour. No drug‐related bleeding events occurred. Conclusions: Favorable PK/PD properties of cangrelor 0.5 µg/kg/min dosing and safety profile warrant further evaluation in neonates following palliative cardiac procedures. Abstract : Summary of enrolled patients characteristics and PK / PD analyses for the 2 cangrelor dosing cohorts.